The Influence of Employee Engagement and Self-Efficacy on Employee Performance Through Innovative Work Behavior at Pt Asam Jawa Medan - Zhafirah Hanan; Ritha F. Dalimunthe; Yeni Absah (East Asian Journal of Multidisciplinary Research, 2024)
This study aims to examine how employee engagement and self-efficacy affect employee performance through innovative work behavior at PT Asam Jawa Medan. It is categorized as quantitative descriptive research. The sample included 125 respondents selected using a non-probability sampling method. Data analysis was performed using both the outer model and inner model with the SmartPLS program. The results indicate that employee engagement, self-efficacy, and innovative work behavior positively and significantly impact employee performance. However, employee engagement has a negative and insignificant effect on innovative work behavior and does not significantly influence employee performance through innovative work behavior.